2023
DOI: 10.1002/rnc.6760
|View full text |Cite
|
Sign up to set email alerts
|

Event‐triggered control of Takagi‐Sugeno fuzzy systems under deception attacks

Abstract: This article handles the problem of periodic event-triggered control co-design for the stabilization of Takagi-Sugeno fuzzy models subject to stochastic deception attacks whose occurrence follows a given Bernoulli distribution.A novel delay-dependent condition is presented to simultaneously design the event-triggering mechanism and the state-feedback controller to ensure the local mean-square asymptotic stability of the closed-loop system. The co-design condition is derived as linear matrix inequalities by con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Nonlinearity exists throughout various practical systems and can affect the dynamic characteristics of systems, and many related studies have been reported. [1][2][3][4][5][6] The existence of nonlinearity inevitably brings great obstacles to system analysis and synthesis, because accurate mathematical models of nonlinear systems are often hard to establish, and traditional linear system methods usually have difficulty managing them. Takagi-Sugeno (T-S) fuzzy model, 7 due to its strong capability of approximating nonlinearity, has been recognized as an efficient technique to resolve this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinearity exists throughout various practical systems and can affect the dynamic characteristics of systems, and many related studies have been reported. [1][2][3][4][5][6] The existence of nonlinearity inevitably brings great obstacles to system analysis and synthesis, because accurate mathematical models of nonlinear systems are often hard to establish, and traditional linear system methods usually have difficulty managing them. Takagi-Sugeno (T-S) fuzzy model, 7 due to its strong capability of approximating nonlinearity, has been recognized as an efficient technique to resolve this problem.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely acknowledged in the literature that LMI is a essential tool for addressing control problems in various fields. For example, it plays a significant role in event-triggered control, 17 gain-scheduled control for linear parameter-varying systems, 18 data-driven control, 19 and fault-tolerant control, 20 to name a few.…”
Section: Introductionmentioning
confidence: 99%